The influence of brine graduation towers on biometeorological conditions, on the example of Ciechocinek spa town (Poland) - Kejna, Marek; Pospieszyńska, Aleksandra; Becker, Marta (Bulletin of Geography. Socio-economic Series, 2022)
The paper provides an analysis of the influence of brine graduation towers on biometeorological conditions, on the basis of the example of Ciechocinek – a spa town in Poland. Using the records of air temperature and relative air humidity in the years 2018-2020 at two locations near Graduation Tower 1 and at the reference site near Spa Hospital No. 1 it was demonstrated that the graduation towers caused a mean drop in air temperature of 0.5–0.7°C with maximum diff erences 7.5°C. The average humidity due to brine evaporation was 3.6–4.6% higher, but maximum differences exceeded 30%. Based on mobile measurements the effects of the graduation tower were found to be limited to its vicinity, where air temperature was lower and humidity higher. The distribution of air temperature and humidity changed depending on wind direction. Cooler and more humid air was carried downwind of the graduation tower. The calculated biometeorological indices showed that neutral, comfortable or refreshing conditions prevailed at the graduation tower and the sensation of heat or thermal stress leading to body overheating was less frequent.